2018
DOI: 10.1177/1475921718804466
|View full text |Cite
|
Sign up to set email alerts
|

Strain and crack analysis within concrete members using distributed fibre optic sensors

Abstract: This article presents laboratory tests, with the purpose being to verify the suitability of standard optical fibres in a tight jacket for advanced strain analysis within concrete members. An optical reflectometer was used to enable the optical signal to be processed on the basis of the Rayleigh scattering phenomenon, so that strains and/or temperature changes were determined along the length of the measuring fibre. The measurements were carried out continuously in a geometrical sense (distributed measurements)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 19 publications
3
61
0
Order By: Relevance
“…Data obtained after statistical analysis will help prepare an experiment on the impact of vibrations on steel to concrete adherence at the time of its bonding. Similar research concerning control of concrete properties at early stages of setting was already provided by authors of article [13].…”
Section: Motivation and Scope Of The Studysupporting
confidence: 60%
“…Data obtained after statistical analysis will help prepare an experiment on the impact of vibrations on steel to concrete adherence at the time of its bonding. Similar research concerning control of concrete properties at early stages of setting was already provided by authors of article [13].…”
Section: Motivation and Scope Of The Studysupporting
confidence: 60%
“…With the entire complicated phenomenon, monitoring the crack openings quantitatively using an optical cable bonded along a host material is still a challenge and the idea of measuring strain near cracks is always a complicated problem [19]. Recently, methods of estimating crack openings from distributed strain measurements were presented whether by combination to finite element models [15,20] or through calculation of the optical fiber elongation by summing strain gradients [17,21,22]. However, the limitations of these methods prevailed in the cases of multiple crack propagation and until a certain crack opening limit.…”
Section: Introductionmentioning
confidence: 99%
“…Distributed optical fiber sensors (DOFS) are modern-day cutting-edge monitoring tools that are quickly acquiring relevance in the structural and civil engineering field [ 3 ]. These are very thin glass wires able to accurately measure strains (down to 1 µε), temperature and vibration in 2 or even 3 dimension [ 4 ]. This can be achieved in a completely-distributed manner (modern interrogation units can attain a spatial resolution of 0.63 mm) and with measurement frequencies of 250 Hz [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases the DOFS are attached directly to the surface of the reinforcement-bars (rebars) before the latter are embedded inside concrete. Multiple studies [ 4 , 8 , 9 , 10 , 11 ] have demonstrated that the technique with which this bonding is achieved has a prominent role in the quality of the extracted data. Indeed, the highly sensitive nature of these hair-like fibers intrinsically exacerbates the probability of its malfunctioning and/or rupture during the concrete casting, maneuvering and testing phase.…”
Section: Introductionmentioning
confidence: 99%